(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The audit committee has received considerable attention from international institutions and researchers as a result of financial failures and the collapse of major international companies, especially cases of manipulation and misinformation in the financial statements, due to the role played by one of the mechanisms of control of economic entities to increase disclosure and credibility of information published, In overseeing the preparation of financial reports, following up the internal auditing functions, supporting the external auditor and enhancing his independence, and strengthening the shareholders’ confidence in the economic entity. The two researchers prepared the applied side of the research by applying a proposed model based on the analysis of the control activities and linking them to the requirements of the committee at Ashur International Bank. The research has reached a set of conclusions that can be summarized as follows: (1) There are several requirements for the audit committee to carry out its audit functions in accordance with the approved supervisory activities, notably the integrity of the financial statements and accounting policies, adherence to the rules and regulations, (2) By examining the activity controls, the gap of performance was 29% for the savings transaction, 38% for Commercial nots transaction.